On families of K3 surfaces with real multiplication - Bert van Geemen; Matthias Schütt (Forum of Mathematics, Sigma)
We exhibit large families of K3 surfaces with real multiplication, both abstractly, using lattice theory, the Torelli theorem and the surjectivity of the period map, as well as explicitly, using dihedral covers and isogenies.